2021
DOI: 10.1016/j.cub.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 and its BORG2 and BORG3 effectors control the subcellular localization of septins between actin stress fibers and microtubules

Abstract: Highlights d Septins relocalize from actin stress fibers to microtubules upon paclitaxel treatment d BORG2/3 knockdown mimics paclitaxel effect and initiates drug resistance d BORG2/3 overexpression prevents paclitaxel-mediated septin relocalization d Active Cdc42 controls BORG2 and septin localization at stress fibers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 79 publications
1
52
0
Order By: Relevance
“…The findings of this study lead to several remaining open questions. In the absence of the identification of actin-binding domains on septins, it is still unclear if SF decoration by septins in cells reflects direct septin-actin interactions, or if such binding occurs through myosin-II or/and Borg proteins (Calvo et al, 2015; Farrugia et al, 2020; Joberty et al, 2001; Joo et al, 2007; Liu et al, 2014; Mostowy et al, 2010; Salameh et al, 2021). The fact that septins are found only on contractile SFs lets one suppose that myosin-II related signaling might be involved in their recruitment to SFs but this remains to be shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study lead to several remaining open questions. In the absence of the identification of actin-binding domains on septins, it is still unclear if SF decoration by septins in cells reflects direct septin-actin interactions, or if such binding occurs through myosin-II or/and Borg proteins (Calvo et al, 2015; Farrugia et al, 2020; Joberty et al, 2001; Joo et al, 2007; Liu et al, 2014; Mostowy et al, 2010; Salameh et al, 2021). The fact that septins are found only on contractile SFs lets one suppose that myosin-II related signaling might be involved in their recruitment to SFs but this remains to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that septins can associate both with actin and microtubules in cells (Bowen et al, 2011; Nagata et al, 2004; Nagata et al, 2003; Spiliotis et al, 2008; Spiliotis et al, 2005; Surka et al, 2002; Verdier-Pinard et al, 2017). The microtubule-binding domain on septins was identified recently (Kuzmic et al, 2022), but actin-binding domains have not yet been identified making it unclear if actin-septin binding involves direct interactions, or if such binding occurs through myosin-II (Joo et al, 2007; Mostowy et al, 2010) or/and Borg proteins (Calvo et al, 2015; Farrugia et al, 2020; Joberty et al, 2001; Liu et al, 2014; Salameh et al, 2021). Similarly, although recombinant and cell-purified mammalian septins bind lipid membranes in the absence of other physiological partners (Bridges et al, 2016; Dolat and Spiliotis, 2016; Szuba et al, 2021; Tanaka-Takiguchi et al, 2009; Yamada et al, 2016), whether there is direct septin-membrane binding in cells has not been formally shown; the identification of the membrane-binding site of septins is a matter of debate (Cavini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Cdc42 cause a loss of septin filaments ( Joberty et al, 2001 ). A recent study shows that Cdc42 controls the subcellular localization of septins between actin stress fibers and microtubules ( Salameh et al, 2021 ).…”
Section: Septins In Endothelial Cellsmentioning
confidence: 99%
“…Anita Baillet (Université Paris-Saclay, INSERM, France) found that the interplay between septins, actin and microtubules can be regulated by the nucleotide state of Cdc42 and its downstream effectors of the BORG family. Indeed, Taxol ®induced Cdc42 inactivation triggers the release of BORG2 from stress fibers and its subsequent proteasome-mediated degradation, resulting in the striking relocalization of septins from actin to microtubules (Salameh et al, 2021). Folma Buss (University of Cambridge, UK) spoke about their work that identified LRCH3 not only as a novel adaptor protein linking the actin-based motor MYO6 and the RhoGEF DOCK7 and forming the septin DISP complex, but also as a novel regulator of septin organization (O'Loughlin et al, 2018).…”
Section: Septin Compartmentalization and Related Functionsmentioning
confidence: 99%